대학생의 학습전략과 부정적 정서, 학업적·사회적 적응이 성적에 미치는 영향: 성별의 조절효과 - 박완성; 정구철; Park, Wan-Sung; Jeong, Goo-Churl (한국콘텐츠학회 논문지, 14(3), 2014)
This research was conducted to verify the moderating effect of gender, which impacts learning strategy, negative emotions, and influence that university life adjustment of undergraduates has on academic achievement. Therefore, this survey was conducted on learning strategy and negative emotion in February, targeting 654 freshmen of a university in Seoul on their academic and social adaptation and grades which has been measured and analyzed three months later at the end of the term. The moderating effect according to genders was analyzed through hierarchical regression analyses, and diagram was presented after conducting the simple gradient verification as a post analysis on interactive effect. As a result of analysis, although learning strategy and academic adaptation was appeared to be significantly affecting grades regardless of gender, the impact of negative emotions on academic achievement were significant only to females, and the impact of social adaptation on academic achievement was significant only to males, which enabled the researchers to confirm the regulation effects on different genders. The implications and proposal for a follow-up study about learning strategy, emotion, and adaptation based on the research resulted in the discussion of academic achievement in university. 본 연구는 대학생들의 학습전략과 부정적 정서, 대학생활적응이 성적에 미치는 영향에 있어서 성별의 조절효과를 검증하기 위해 수행되었다. 이를 위해 서울시에 소재한 1개 대학교의 신입생 654명을 대상으로 2월에 학습전략과 부정적 정서를 조사하였으며, 3개월 후 학기 말에 학업적 사회적 적응과 성적을 측정하여 분석하였다. 성별에 따른 조절효과는 위계적 회귀분석을 통해 분석하였으며, 상호작용 효과의 사후분석으로 단순기울기 검증을 수행한 후 도식으로 제시하였다. 분석결과 학습전략과 학업적 적응은 성별에 관계없이 모두 성적에 유의한 영향을 미치는 것으로 나타났으나, 부정적 정서가 성적에 미치는 영향은 여자에게서만 유의하였고, 사회적 적응이 성적에 미치는 영향은 남자에게서 유의하게 나타나 성별의 조절효과를 확인할 수 있었다. 이러한 연구결과를 바탕으로 대학에서의 학업적 성취에 학습전략과 정서 및 적응에 대한 시사점 및 후속연구에 대한 제언을 논의하였다.